Decision analysis on the use of figma to improve learning effectiveness at Saengsattha School Thailand using the AHP Method - Defri Aldi; Mhd. Basri; Lutfi Basit (Educenter : Jurnal Ilmiah Pendidikan, 2026)
The development of digital media-based learning requires the selection of platforms that are not only easy to use, but also capable of supporting interactivity, collaboration, and providing a real impact on learning outcomes. However, the selection of digital learning media in schools is often not based on systematic and measurable decision analysis. This condition creates a need for objective evaluation of the effectiveness of digital media used in the learning process. This study aims to analyze the effectiveness of using Figma as a digital learning medium at Saengsattha School in Thailand. This study uses a descriptive quantitative approach with data collection through a five-point Likert scale questionnaire involving 100 respondents, consisting of 10 teachers and 90 students. Data analysis was performed using the Analytical Hierarchy Process (AHP) method to determine the weight of importance of four main criteria, namely ease of use, interactivity, collaboration, and impact on learning outcomes and user satisfaction. The results showed that Figma obtained a final score of 4.06 and was categorized as effective, with the criteria of impact and user satisfaction as the most dominant factors. These findings indicate that Figma is suitable for use as a digital learning medium and that AHP can be a systematic method to support decision-making in selecting digital learning media in schools.